1995
DOI: 10.2151/jmsj1965.73.1_59
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic and Non-Hydrostatic Simulations of Moist Convection

Abstract: Comparative experiments of moist convection using hydrostatic and non-hydrostatic models are performed to study the suitability of the hydrostatic approximation for a high-resolution model when the grid size falls below 20km. The moist convection in the models is treated by the use of an explicit warmrain process predicting cloud water and rainwater as well as by a semi-explicit scheme consisting of the warm-rain process and moist convective adjustment. The differences between the experiments with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
(31 reference statements)
3
9
0
Order By: Relevance
“…One of the properties of hydrostatic systems is supposed to be the overestimation of convective precipitation amount and area compared to nonhydrostatic systems (Kato and Saito, 1995;Kato, 1997). When looking at total precipitation over land and comparing it with values from IMERG, it looks like IFS is overestimating convective precipitation.…”
Section: Total Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the properties of hydrostatic systems is supposed to be the overestimation of convective precipitation amount and area compared to nonhydrostatic systems (Kato and Saito, 1995;Kato, 1997). When looking at total precipitation over land and comparing it with values from IMERG, it looks like IFS is overestimating convective precipitation.…”
Section: Total Precipitationmentioning
confidence: 99%
“…But then again, Dudhia (1993) found only little differences between the hydrostatic and the nonhydrostatic solution for a cold front with grid spacing of 6.5 km. Kato and Saito (1995) performed idealized moist convection simulations with grid spacings of 20 km, 10 km, and 5 km and found that the hydrostatic model without parameterized deep convection overdevelops updrafts and overestimates convective precipitation amount and area. These results were later confirmed for a real-world case from Kato (1996).…”
mentioning
confidence: 99%
“…This paper seeks to address these questions through both analytical solutions to the relevant equations of motion as well as cloud‐resolving numerical simulations, run with an atmospheric model equipped with both hydrostatic and nonhydrostatic solvers. Of course, similar approaches have been taken by previous authors (W97; Kato & Saito, ; Morrison, ; Orlanski, ; Pauluis & Garner, ), so we must build on these prior studies in meaningful ways. We do so by first taking advantage of the aforementioned computer power to explore much finer resolutions ( dx100 m) than these previous studies ( dx2 km), ideally probing down to the inner edge of the gray zone.…”
Section: Introductionmentioning
confidence: 97%
“…As might be expected, real-case simulations demonstrated that nonhydrostatic mesoscale models are superior to hydrostatic models in high-resolution precipitation forecasts [14][15][16][17]. However, it should be noted that such simulations were conducted with a grid spacing smaller than 10 km, which is traditionally considered the hydrostatic limit in the absence of latent heat release [18]. Meanwhile, Dudhia [19] identified a "gray zone" of the dynamics and it remains unclear whether nonhydrostatic dynamics should be applied within this zone.…”
Section: Introductionmentioning
confidence: 92%